Analytical determination of permeability of porous fibrous media with consideration of electrokinetic phenomena - Yang, J. (2013)
Flow behavior in porous fibrous media with consideration of electrokinetic phenomena is investigated based on a linearized Poisson–Boltzmann equation and Navier–Stokes equation. An analytical solution of effective permeability of porous fibrous media as functions of porosity, dimensionless local averaging net charge density and dimensionless electric resistance number is derived in this paper. The influences of the electrokinetic phenomena can be measured by the dimensionless electric resistance number, which is proportional to the square of the liquid dielectric constant, the solid surface Zeta potential and inversely proportional to the liquid dynamic viscosity, electric conductivity and the square of the maximum pore radius. The analytical results show that when the dimensionless electric resistance number is small and the porosity is large, the dimensionless total flow rate shows a nearly uniform distribution. When the dimensionless electric resistance number is large, the resistant effects of the electrical double layer (EDL) become so significant that the superficial velocity decreases. The effective permeability of the porous fibrous media decreases correspondingly. Furthermore, the theoretical predicted effective permeability values are compared with experimental data, and good agreement is observed between the two. It shows that the mathematical model for the effective permeability of porous fibrous media with consideration of electrokinetic phenomena is satisfactory.